The Effect Of Aqueous Nigella Sativa Extract On Hypothyroidism Which Induced In White Mices (Journal of Hama University, 2022)
This study aimed to determine The effect of aqueous Nigella sativa seeds extract on level s of FT3,FT4,TSH in the blood serum of induced oral hypothyroidism White adult mice and promoting it's therapeutic capacity . This study included 30 female white mice( Balb/c strain )which were divided into three experimental group ,10 mice in each :the first group was the physiological control was treated with oral cavity 0,9% Nacl until the end of the experiment, While the second group was the pathologyical control was treated with oral cavity of methimazole in dose (0,05mg/kg) for three weeks,and, the third group was treatment group were treated whith cavity of 400mg/kg aqueous extract of nigella sativa for4 weeks .at the end of experiment e blood simplees were collected for biochemical analysis. Result showed that the aqueous extract of nigella sativa seeds has positive effect on hypothyroidism ,as the level of FT3 were significantly increase(p